Advances in stress and depression research. Issue 1 (3rd January 2023) - LeMoult, Joelle; Battaglini, Ashley M.; Grocott, Bronwen; Jopling, Ellen; Rnic, Katerina; Yang, Lisa
Abstract : Purpose of review: Stress plays a central role in the onset and course of depression. However, only a subset of people who encounter stressful life events go on to experience a depressive episode. The current review highlights recent advances in understanding when, why, and for whom the stress-depression link occurs, and we identify avenues for future research. Recent findings: In the last 18 months, researchers have taken a more nuanced perspective on the biopsychosocial mechanisms critical to the stress–depression link. For example, examination of specific facets of emotion regulation, including emotion regulation flexibility and interpersonal emotion regulation, has been critical to understanding its role in depression. Similarly, refined investigations of social support allowed researchers to identify distinct – and occasionally opposite – outcomes depending on the context or manner in which the support was provided. Researchers also documented that the stress–depression link was enhanced by dysregulation of several stress-sensitive biological systems, such as the immune system, microbiome, endocrine system, and neuroanatomical substrates. Summary: Recent studies highlight the importance of adopting a nuanced understanding of mechanisms and moderators that explain the stress–depression link. We also encourage continued engagement in collaborative, open science that uses multiple methods to study the full breadth of human diversity.